Implementation of the Business Model Canvas Strategy for MSMEs in Karanganyar Regency - Augtiah, Imfrianti; Ariyadi, Muhammad Yusuf; Bintang, Rauhulloh Ayatulloh Khomeini (Jurnal EMT KITA, 2023)
MSMEs in Indonesia contribute to national income with significant growth from year to year. The role of government, both central and regional, is very necessary in mentoring programs for MSMEs, from various aspects of development such as improving product quality, price competition, business management, marketing, financial management, and developing the quality of human resources. The Karanganyar Central Statistics Agency (BPS) stated that approximately 60% of MSMEs are developing significantly and making a lot of contributions to the surrounding community but their business performance is still low. The aim of this research is to describe research on the Implementation of the Business Model Canvas in MSMEs in Karanganyar Regency. The number of MSMEs that are developing after the Covid 19 pandemic has the impact of continuing to grow but their business performance is still low. Therefore, the author is very interested in raising the theme of Implementing the Canvas Model Business Strategy in Efforts to Sustain MSMEs in the future. This research method uses a descriptive qualitative method and tends to use qualitative research. In this study, a purposive sampling technique was used to determine respondents who could be selected as samples. The data source that will be used is primary data with interviews assisted using questions via a questionnaire delivered directly. The questionnaire contains closed questions where in answering them the researcher provides guidance and assistance, if someone experiences difficulties, they will get direction. Respondents will be taken from business actors in Karanganyar Regency, totaling 21 respondents from UKM circles. A persuasive approach will be taken to obtain the necessary data. The findings in this research are that business actors were able to survive during the pandemic by implementing the Business Model Canvas strategy even though they had not yet 100 percent conceptualized this strategy in their business